A Refined Protocol for Coronary Artery Ligation in the Neonatal Mouse. Issue 2 (22nd February 2021) - De Villiers, Carla; Riley, Paul R.
Abstract: The neonatal mouse heart can regenerate following myocardial infarction (MI), a capacity that is lost after 7 days, providing a model system to study tissue regeneration and the transition to adult wound healing. MI can be induced in neonatal mice surgically by coronary artery ligation. In this protocol, neonates are anesthetized using a combination of inhaled isoflurane anesthesia and induced hypothermia, a significant ethical refinement over previous protocols. A lateral thoracotomy is performed, and an 8‐0 suture is used to ligate an area below the left atrium to induce MI. The ribs and skin are closed using 7‐0 sutures, and the pup is rapidly rewarmed with a supply of oxygen. Once recovered, the pup is cleaned and rolled in a fecal bath to mask the smell of surgical interference before being returned to the mother. The surgical procedure is expected to take 10 to 15 min per pup, with a further 5 min for recovery. A dedicated assistant for recovery of pups is recommended to streamline the procedure. © 2021 Wiley Periodicals LLC.